Progesterone, oestradiol, luteinizing hormone and follicle stimulating hormone profiles and their relationship with superovulatory response and quality of embryos in crossbred cows treated with folltropin and prostaglandin F2 α - AROSH, A JOE; SAKHILA, K; DEVANATHAN, T G; KATHIRESAN, D (The Indian Journal of Animal Sciences, 2014)
Crossbred cows (8) were selected and their oestrus was synchronized with double injections of PGF2α at 12 days apart. The induced oestrus was considered as day 0. The superovulation was induced with folltropin-V on day 9 of the oestrous cycle. The characteristics of oestrus were studied. The embryos were collected non surgically on day 7 post oestrus. The mean number of ovulations, unovulatory follicles, total embryos, transferable embryos, nontransferable embryos and unfertilized oocytes were 10.88 ± 1.02, 0.63 ± 0.03,8.00 ± 0.88,5.88 ± 0.81, 1.63 ± 0.02 and 0.50 ± 0.01 respectively. The onset, duration and intensity of oestrus were positively correlated with the number of ovulations. total embryos and transferable embryos. The number of ovulations. total embryos and transferable embryos were significantly (P